A response to yet another defence of ECT in the absence of robust efficacy and safety evidence. (15th February 2022) - Read, John
Abstract: It is estimated that electroconvulsive therapy is still administered to approximately a million people a year. It involves passing enough electric current through the human brain, eight to twelve times, to cause convulsions, in the hope of somehow alleviating emotional suffering, primarily depression. There have only ever been 11 placebo-controlled studies (where general anaesthesia is administered but the electric shock is withheld), all of which were pre-1986, had very small sample sizes and were seriously methodologically flawed. Five of these studies found no difference between the two groups at the end of treatment, four found ECT produced better outcomes for some patients, and two produced mixed results, including one where psychiatrists' ratings produced a difference, but the ratings of nurses and patients did not. In the 80 years since the first ECT no studies have found any evidence that ECT is better than placebo beyond the end of treatment. Nevertheless, all five meta-analyses relying on these studies have somehow concluded that ECT is more effective than placebo despite the studies' multiple failings. Meanwhile, evidence of persistent or permanent memory loss in 12% to 55% of patients has accumulated. Attempts to highlight this failure of ECT proponents to provide robust evidence that their treatment is effective and safe are routinely dismissed, diminished, denied and denounced. This paper responds to one such attempt, by Drs Meechan, Laws, Young, McLoughlin and Jauhar, to discredit two systematic reviews of the eleven pre-1986 studies, in 2010 and 2019, the latter of which also reviewed five meta-analyses that had ignored the studies' failings. The criticisms and claims of the recent crtiique of the two systematic reviews are examined in detail, by the first author of both reviews, for accuracy, relevance and logic. The critique is found to include multiple errors, misrepresentations, omissions, inconsistencies and logical flaws. It is concluded that Meechan et al . fail to make a fact-based, coherent argument against suspending ECT pending a series of large, carefully designed placebo-controlled studies to establish whether ECT does have any beneficial effects against which to weigh the significant established adverse effects.